Halofuginone Synergistically Enhances Anti-Proliferation of Rapamycin in T Cells and Reduces Cytotoxicity of Cyclosporine in Cultured Renal Tubular Epithelial Cells - Chu, Tony L. H.; Guan, Qiunong; Nguan, Christopher Y. C.; Du, Caigan (PLOS ONE, 2015)
Both rapamycin (RAPA) and cyclosporin A (CsA) are commonly used for immunosuppression, however their adverse side effects limit their application. Thus, it is of interest to develop novel means to enhance or preserve the immunosuppressive activity of RAPA or CsA while reducing their toxicity. Halofuginone (HF) has been recently tested as a potential immunosuppressant. This study investigated the interaction of HF with RAPA or with CsA in cell cultures. Cell proliferation in cultures was determined using methylthiazol tetrazolium assay, and cell apoptosis assessed by flow cytometric analysis and Western blot. The drug-drug interaction was determined according to Loewe’s equation or Bliss independence. Here, we showed that addition of HF to anti-CD 3 antibody-stimulated splenocyte cultures induced synergistic suppression of T cell proliferation in the presence of RAPA, indicated by an interaction index (γ) value of < 1.0 between HF and RAPA, but not in those with CsA. The synergistic interaction of RAPA with HF in the suppression of T cell proliferation was also seen in a mixed lymphocyte reaction and Jurkat T cell growth, and was positively correlated with an increase in cell apoptosis, but not with proline depletion. In cultured kidney tubular epithelial cells, HF attenuated the cytotoxicity of CsA. In conclusion, these data indicate that HF synergistically enhances anti-T cell proliferation of RAPA and reduces the nephrotoxicity of CsA in vitro, suggesting the potential use of HF for enhancing anti-T cell proliferation of RAPA and reducing CsA-mediated nephrotoxicity.